1975
DOI: 10.1113/expphysiol.1975.sp002310
|View full text |Cite
|
Sign up to set email alerts
|

Flow in Glass Models of Arterial Bifurcations and Berry Aneurysms at Low Reynolds Numbers

Abstract: Using the dye injection technique, flow at low Reynolds numbers was studied in glass models which simulated arterial bifurcations of varying angles and had varying bluntness of the apex or crotch. Forks bearing small saccular evaginations simulating berry aneurysms were investigated similarly. At quite low Reynolds numbers in all the models small wave motion was observed at the forks. At higher Reynolds numbers and below the critical values for turbulence, larger vortices akin to a K'arman vortex street were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The minor variations in dye intensity or rippling have been observed at low Reynolds number beyond a stenosis (Johansen, 1929), in glass models simulating arterial bifurcations (Stehbens, 1975) and in a thin film of liquid flowing down a vertical plate (Binnie, 1957). These ripples precede coarser periodic flow disturbances either at higher flow velocities or as the result of external disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The minor variations in dye intensity or rippling have been observed at low Reynolds number beyond a stenosis (Johansen, 1929), in glass models simulating arterial bifurcations (Stehbens, 1975) and in a thin film of liquid flowing down a vertical plate (Binnie, 1957). These ripples precede coarser periodic flow disturbances either at higher flow velocities or as the result of external disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…This would have had the effect of an ampulla at the commencement of the stem. Just as it has been shown that the radius of curvature or bluntness of the apex of a bifurcation influences the onset of flow disturbances (Stehbens, 1975), so in reverse flow through the models, bluntness of the apex and the cross-sectional area at the confluence of the two tributaries affect flow at that site. Minor variations in architecture of the models at the junction may therefore influence flow and probably account for some inconsistencies in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in vivo, velocity fluctuations have been found in some patients intra-operatively prior to aneurysm clipping. However, their association with rupture has not been determined [9][10][11][12]. Similarly, in vitro particle image velocimetry measurements [13] and flow visualization in experimental glass models have also noted unstable flow within vasculature models [12,14,15].…”
Section: Introductionmentioning
confidence: 99%